2020
DOI: 10.1001/jama.2020.12528
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Cases and Deaths in Federal and State Prisons

Abstract: Novel coronavirus disease 2019 (COVID-19) represents a challenge to prisons because of close confinement, limited access to personal protective equipment, and elevated burden of cardiac and respiratory conditions that exacerbate COVID-19 risk among prisoners. 1 Although news reports document prison outbreaks of COVID-19, systematic data are lacking. 2 Relying on officially reported data, we examined COVID-19 case rates and deaths among federal and state prisoners. Methods | Counts of COVID-19 cases and presume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
296
1
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 331 publications
(312 citation statements)
references
References 2 publications
10
296
1
5
Order By: Relevance
“…31 By contrast, jails and prisons in the USA have not depopulated at the same scale as other countries. [46][47][48][49]51,52 Additionally, amid this exponential increase in cases and the casefatality rate among incarcerated people, 39 current federal guidance continues to withhold expanded testing approaches that could provide invaluable guidance for population management strategies inside correctional facilities. 28 The eighth amendment of the US Constitution clearly guarantees freedom from cruel and unusual punish ments; however, the illness and deaths caused by COVID19 in prisons show inherent cruelties within the correctional systems of the USA.…”
Section: Personal Viewmentioning
confidence: 99%
“…31 By contrast, jails and prisons in the USA have not depopulated at the same scale as other countries. [46][47][48][49]51,52 Additionally, amid this exponential increase in cases and the casefatality rate among incarcerated people, 39 current federal guidance continues to withhold expanded testing approaches that could provide invaluable guidance for population management strategies inside correctional facilities. 28 The eighth amendment of the US Constitution clearly guarantees freedom from cruel and unusual punish ments; however, the illness and deaths caused by COVID19 in prisons show inherent cruelties within the correctional systems of the USA.…”
Section: Personal Viewmentioning
confidence: 99%
“…As noted, BC Corrections' predominant use of single-bunking and induction units is contingent on low provincial custody counts (BC Corrections, 2020a). In the months ahead, crime rates, police decision-making, increased court activity, judicial decision-making, community infection rates, and other factors will fundamentally determine whether BC Corrections can continue to utilize the strategies they have implemented to address the pandemic and that have to date been so effective in preventing major outbreaks of COVID-19 in custody centers while other correctional authorities have failed to do so (see Franco-Paredes et al, 2020;Marcum, 2020;Oladeru et al, 2020;Ouellet & Loiero, 2020;Saloner et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Health and justice officials across North America have described correctional institutions as petri dishes for the transmission of COVID-19 (see e.g., Paynter, 2020). Correctional authorities have struggled to implement strategies to mitigate infection rates within custodial populations (Franco-Paredes et al, 2020;Marcum, 2020;Oladeru et al, 2020;Ouellet & Loiero, 2020;Saloner et al, 2020). A preliminary analysis of COVID-19 infection rates among incarcerated populations in Canada conducted in July 2020 found that infection rates were up to five times higher in provincial custodial institutions and nine times higher in federal correctional institutions than infection rates in the community (Ouellet & Loiero, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All Rights Reserved http://journals.ke-i.org/index.php/mra 42,107 cases of COVID-19 and 510 deaths among 1,295,285 prisoners with a case rate of 3,251 per 100,000 prisoners," a rate that "was 5.5 times higher than the US population case rate of 587 per 100,000." 153 When accounting for age and sex distributions in the prison population, "the adjusted death rate… was 3.0 times higher than would be expected" than that of the general public. Based on this data, "prisoners are hospitalized and dying more frequently when infected."…”
Section: Incarcerated Populationsmentioning
confidence: 98%